Description Of Risk Factors Associated With The Incident Of Urinary Tract Infections In Pregnant Women - Dhea Dwi Anggraini; Anna Sari Dewi; Muhammadong, Muhammadong (Sean Institute, 2024)
Throughout the world, infectious diseases are a problem that affects both developed and developing countries. After lung infections, urinary tract infections rank as the second most common health problem. Anatomically, women are more likely than men to experience urinary tract infections due to the shorter urethra in women. Pregnant women's bodies undergo structural and physiological changes that increase their chances of developing urinary tract infections. In pregnant women alone, there is a 20% incidence of urinary tract infections (UTI). Literature review with narrative review design.The results obtained were that pregnant women were more at risk of developing UTIs.Oobesity, multiparity, holding back urination, sexual relations and individual hygiene are some of the risk factors that will occurcan increase the risk of a more serious UTI.